2017
DOI: 10.1111/mcn.12550
|View full text |Cite
|
Sign up to set email alerts
|

Characterising infant and young child feeding practices and the consumption of poultry products in rural Tanzania: A mixed methods approach

Abstract: Suboptimal breastfeeding practices, early initiation of complementary feeding, and monotonous cereal-based diets have been implicated as contributors to continuing high rates of child undernutrition in sub-Saharan Africa. Nutrition-sensitive interventions, including agricultural programs that increase access to nutrient-rich vegetables, legumes, and animal-source foods, have the potential to achieve sustainable improvements in children's diets. In the quest to evaluate the efficacy of such programs in improvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Instead, smallholders demonstrated a strong preference for leaving eggs from village chickens to hatch, increasing flock sizes, and allowing them to more readily sell birds as needed (Dumas et al, ). This phenomenon has been reported elsewhere (de Bruyn et al, ; Dumas et al, ; Gueye, ; Olney, Vicheka, Kro, & Chakriya, ) and is a major limitation to the use of village poultry as a tool for increasing egg availability and consumption. Additionally, there is an emerging concern that free‐ranging poultry can negatively affect child nutrition outcomes by exposing them to zoonotic pathogens that cause clinical disease (e.g., diarrhoea; Zambrano, Levy, Menezes, & Freeman, ) or environmental enteric dysfunction (Gelli et al, ; George, Oldja, Biswas, Perin, Lee, Ahmed, et al, ; George, Oldja, Biswas, Perin, Lee, Kosek, et al, ; Headey & Hirvonen, ; Marquis et al, ; Ngure et al, ).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Instead, smallholders demonstrated a strong preference for leaving eggs from village chickens to hatch, increasing flock sizes, and allowing them to more readily sell birds as needed (Dumas et al, ). This phenomenon has been reported elsewhere (de Bruyn et al, ; Dumas et al, ; Gueye, ; Olney, Vicheka, Kro, & Chakriya, ) and is a major limitation to the use of village poultry as a tool for increasing egg availability and consumption. Additionally, there is an emerging concern that free‐ranging poultry can negatively affect child nutrition outcomes by exposing them to zoonotic pathogens that cause clinical disease (e.g., diarrhoea; Zambrano, Levy, Menezes, & Freeman, ) or environmental enteric dysfunction (Gelli et al, ; George, Oldja, Biswas, Perin, Lee, Ahmed, et al, ; George, Oldja, Biswas, Perin, Lee, Kosek, et al, ; Headey & Hirvonen, ; Marquis et al, ; Ngure et al, ).…”
Section: Introductionsupporting
confidence: 61%
“…Third—perhaps most importantly—as a means of offsetting high flock mortality, smallholders have repeatedly demonstrated a preference for allowing eggs from village chickens to hatch rather than consuming them at home (de Bruyn et al, ; Dumas et al, ; Dumas et al, ; Gueye, ; Olney et al, ). The multipurpose utility of poultry (as a source of food, income, and resilience in the face of shocks) requires a daily cost–benefit analysis on the part of the smallholder, who must weight the many demands of their household in the face of limited resources (Pell & Kristjanson, ).…”
Section: Discussionmentioning
confidence: 99%
“…This supports findings elsewhere in African communities accustomed to high levels of mortality in scavenging chicken flocks, where households prioritize the hatching of eggs for replacement stock and retention of chickens for sale in times over home consumption [ 55 , 56 ]. Previous qualitative work in the study setting found no currently-held beliefs or cultural constraints to explain provide other explanations for infrequent egg consumption [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…This review describes the evolution of PE (in relation to veterinary epidemiology and briefly in relation to public health epidemiology), the underpinning philosophy and principles essential to its effective application, and highlights the importance of gender-sensitive approaches and data triangulation, including conventional confirmatory testing. It discusses the importance of understanding social perceptions and drivers, which is receiving increasing recognition by epidemiologists, and provides examples as to how PE tools are being adapted for an increasingly wide range of settings and endeavors, including: use in food and nutrition security programs ( 5 7 ); One Health activities ( 8 ); wildlife disease surveillance ( 9 ); gender analysis ( 10 , 11 ); communication ( 12 , 13 ); and for monitoring and evaluation ( 14 ).…”
Section: Introductionmentioning
confidence: 99%